Faktor-faktor yang Mempengaruhi Tingkat Pengungkapan Laporan Keuangan Dengan Kepemilikan Institusional Sebagai Variabel Moderasi pada Perusahaan di Bursa Efek Indonesia Tahun 2013 – 2018 - Noviyanti; Afrizal; Asep Machpuddin (Jurnal Akuntansi & Keuangan Unja, 2020)
This study aims to examine the effect of Liquidity, Solvency, Profitability, Company Age, Company Size on the Level of Disclosure of Financial Statements Mandatory moderated by Institutional Ownership of Companies listed on the Indonesia Stock Exchange in 2013 - 2018. The statistical test tool used was Paired Sample T-Test and One Way Anova using the SPPS for Windows Realease 24 program. The results of the t test based on the test showed the influence of Company Age and Debt to Total Asset Ratio on the Level of Disclosure of Obligatory Financial Statements and Institutional Ownership the effect of Company Age and Company Size variables on the level of financial statement Mandatory Disclosures whereas, current Ratio, Return on Asset Ratio, Company Size does not affect the level of financial statement mandatory disclosure. The results of the research based on the f test show the Current Ratio, Debt to Total Asset Ratio, Return on Asset Ratio, Company Age, Firm Size simultaneously affect the Financial Statements Disclosure Level. Keywords: Current Ratio, Debt to Total Asset Ratio, Return on Asset Ratio, Company Age, Company Size, Institutional Ownership and Disclosure of Financial Statements.